2016
DOI: 10.1080/1828051x.2016.1149742
|View full text |Cite
|
Sign up to set email alerts
|

Development and test of a portable device to monitor the health status of Sarda breed sheep by the measurement of the milk electrical conductivity

Abstract: The electrical conductivity (EC) of milk is a parameter which is often used for identifying sub-clinical mastitis in dairy animals. It is widely used for cattle, and is measured either by means of probes integrated into the milking machine or by means of portable devices. However this is not the case for small ruminants, where the available devices are few. The aim of this study is to deepen the knowledge of about the relationship between EC and certain constituents of Sarda sheep milk, and thus to develop a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
2
9
2
Order By: Relevance
“…The negative correlation of EC with the fat content of milk agrees with Caria et al (2016), Prentice (1962), and Mucchetti et al (1994), who stated that fat globules increased the actual distance in the migration of ions that tend to cross over between the 2 electrodes of the conductometer. Albenzio et al (2002), Leitner et al (2004), Bianchi et al (2004), andSantos et al (2007) observed a decline in the fat content of milk from ewes with mastitis, which along with the ion concentration would explain the increase in EC observed in the milk from the infected glands.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The negative correlation of EC with the fat content of milk agrees with Caria et al (2016), Prentice (1962), and Mucchetti et al (1994), who stated that fat globules increased the actual distance in the migration of ions that tend to cross over between the 2 electrodes of the conductometer. Albenzio et al (2002), Leitner et al (2004), Bianchi et al (2004), andSantos et al (2007) observed a decline in the fat content of milk from ewes with mastitis, which along with the ion concentration would explain the increase in EC observed in the milk from the infected glands.…”
Section: Discussionsupporting
confidence: 85%
“…However, they also observed that when taking the difference in EC between both glands of the same animal into account, the outcomes improved considerably (70% sensitivity, 93% specificity, and 89.1% of samples classified correctly for a difference between glands greater than 0.3 mS/cm). The results obtained by Caria et al (2016) were also better than those obtained in this work; they achieved sensitivity and specificity of 73.08% and 75.46%, respectively, setting an EC threshold of 4.84 mS/cm. These results show that for EC to be used as a method for detecting mastitis in sheep, as Díaz et al (2011) also noted, we should develop detection methods that would not be affected by the variations arising in milk EC due to intrinsic animal factors (parity number, milking session, and lactation stage) and not be limited to setting absolute thresholds.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The novelty of our solution is based on the ability to control milk in-flow, working with any small size milking machine, provide three main indicators: overmilking phase alert, milk temperature, subclinical mastitis probability indicator, furthermore, it has the capability for data collection. We observed multiple researches aiming to develop a portable device to monitor the health status based on the threshold value of electrical conductivity (EC) [9]. However, we have not found similar research on the solution for control milk in-flow working with any small size milking machine.…”
Section: Introductionmentioning
confidence: 99%